2016
DOI: 10.3892/mmr.2016.5483
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative PCR marker genes for endometrial adenocarcinoma

Abstract: Abstract. Endometrial adenocarcinoma is a common malignancy in women worldwide, with formation of remote metastasis occurring following oncological treatment. Circulating tumor cells (CTCs) are regarded to be the origin of haematogenous metastasis formation. The present study aimed to identify suitable marker genes using a quantitative polymerase chain reaction (qPCR) approach to detect CTCs from blood samples of patients with endometrial carcinoma. Therefore, RNA was isolated from endometrial adenocarcinoma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(40 reference statements)
1
1
0
Order By: Relevance
“…This hypothesis concerning claudin-4 was also confirmed by the study carried out by Pan et al [128]. In addition, Kölbl et al used claudin-4 with other markers to detect circulating tumor cells (CTCs) [72]. The results showed that claudin-4 expression is increased in most cell lines used in that study, indicating that it might serve as a good marker for detecting CTCs [72].…”
Section: Claudins In Endometrial Cancersupporting
confidence: 55%
See 1 more Smart Citation
“…This hypothesis concerning claudin-4 was also confirmed by the study carried out by Pan et al [128]. In addition, Kölbl et al used claudin-4 with other markers to detect circulating tumor cells (CTCs) [72]. The results showed that claudin-4 expression is increased in most cell lines used in that study, indicating that it might serve as a good marker for detecting CTCs [72].…”
Section: Claudins In Endometrial Cancersupporting
confidence: 55%
“…In addition, Kölbl et al used claudin-4 with other markers to detect circulating tumor cells (CTCs) [72]. The results showed that claudin-4 expression is increased in most cell lines used in that study, indicating that it might serve as a good marker for detecting CTCs [72]. On the other hand, Tessier-Cloutier et al showed that in differentiated and undifferentiated endometrial cancers, claudin-4 expression is absent or very low [73].…”
Section: Claudins In Endometrial Cancermentioning
confidence: 92%